LIMITATION OF THE CRIMINALIZATION OF BUSINESS DECISIONS FROM THE BUSINESS JUDGMENT RULE PERSPECTIVE: A CASE STUDY OF AMSAL SITEPU IN A COMMANDITAIRE VENNOOTSCHAP - Andri Wahyu Putranto; Bhenarido Akbar; Evana Ardelia Rein; Elfani Br Ketaren (Awang Long Law Review, 2026)
This study aims to analyze the limits of criminalization of business decisions from the perspective of the Business Judgment Rule (BJR), using the case study of Amsal Sitepu in a Limited Partnership (CV). The primary focus of the study is to examine the position of BJR in Indonesian corporate law and the conceptual relevance of its application to active partners in CVs who lack the normative protections afforded by Limited Liability Companies. The research method used is a qualitative approach, incorporating juridical-normative methods and case studies, to understand the application of legal principles in practice and identify the boundaries between business risk and criminal liability. This study concludes that the BJR plays a crucial role in limiting the criminalization of business decisions, both normatively within Limited Liability Companies and conceptually against active partners of CVs, in order to maintain a balance between business freedom and legal certainty.